Effect of volume of urine and mass of faeces on N2O and CH4 emissions of dairy-cow excreta in a tropical pasture - Cardoso, Abmael da Silva [UNESP]; Rodrigues Alves, Bruno Jose; Urquiaga, Segundo; Boddey, Robert Michael (Csiro Publishing, 2018)
We aimed to quantify nitrous oxide (N2O) and methane (CH4) emissions as a function of the addition of different quantities of bovine faeces and urine on soil under pasture. Two experiments were performed in randomised complete blocks with five replicates. In the first experiment, the emissions of CH4 and N2O were evaluated for 14 days after the addition of four amounts of faeces (0.0, 1.2, 1.8 and 2.4 kg of fresh faeces per plot), and in a second experiment, N2O emissions were evaluated for 43 days after addition of four volumes of urine (0.0, 1.0, 1.5 and 2.0 L). Urine and faeces came from crossbred (Fresian x Gir) dairy cows fed on pasture and concentrates. N2O emissions from faeces did not alter the emission factor (EF) according to the faeces weight (P = 0.73). N2O-N EF from faeces-N averaged 0.18% (+/- 0.05) of total applied N. The volume of urine applied influenced N2O losses. The EF decreased linearly (P = 0.015) with increasing volumes of urine, being 4.9% (+/- 0.75), 3.36% (+/- 0.7) and 2.43% (+/- 0.46) of N applied emitted as N2O for the 1.0, 1.5 and 2.0 L volumes of urine respectively. The EF from urine was significantly (P < 0.0001) higher than the EF from faeces. There was no change to the CH4 emissions per kilogram of excreta when the amount of faeces added was varied (P = 0.87). However, the CH4 emitted increased linearly with the amount of faeces (P = 0.02). The CH4 EF was estimated to be 0.95 (+/- 0.38) kg/head.year.
Keywords: bovine excrete; N2O emission factor; Pangola grass